Predictors of false-positive stroke thrombectomy transfers. (30th March 2017) - Yi, Julia; Zielinski, Danielle; Ouyang, Bichun; Conners, James; Dafer, Rima; Chen, Michael
Abstract : Background: Most patients with large vessel occlusion (LVO) stroke need to be transferred to receive thrombectomy. To save time, the decision to transfer often relies on clinical scales as a surrogate for LVO rather than imaging. However, clinical scales have been associated with high levels of diagnostic error. The aim of this study is to define the susceptibility to overdiagnosis of our current transfer decision process by measuring the rate of non-treatment transfers, the most common reasons for no treatment and potential predictors. Methods: Clinical and transfer data on consecutive patients transferred to a single endovascular capable centre for possible thrombectomy via stroke code activation were retrospectively reviewed. Whether patients underwent the procedure, why they did not undergo the procedure, and other clinical and logistical predictors were recorded. χ 2 tests and multivariate logistic regression analysis were performed. Results: From 2015 to 2016, 105/192 transferred patients (54%) did not undergo thrombectomy and the most common reason was absence of a LVO found on CTA after transfer (71/104 (68%)). 14/16 (88%) with a National Institutes of Health Stroke Scale (NIHSS) score <10 did not undergo thrombectomy while 41/78 (52%) with a NIHSS>20 underwent thrombectomy (p<0.001). Helicopter use was associated with no treatment (p=0.004) while arrival within 5 hours was associated with treatment (p<0.001). Conclusions: Clinical scales appear to overdiagnose LVO and may be responsible for the majority of our stroke code transfers not undergoing thrombectomy. Primary stroke centres therefore have reason to develop the capability to rapidly acquire and interpret a CTA in patients with suspected LVO prior to transfer. Such efforts may reduce the costs associated with unnecessary thrombectomy transfers.